Sentinel Lymph Node Biopsy in Patients with Breast Cancer: Comparison of Peritumoral and Periareolar Injection - Rosenow, T. (Georg Thieme Verlag KG, 2012)
Introduction: Intradermal periareolar injection technique for sentinel lymph node biopsy (SLNB) may offer an advantage by including multifocal breast cancer as an additional indication. In May 2008 we changed our standard procedure from peritumoral (PT) to periareolar (PA) injection. We compared the results for corresponding periods before and after the change in procedure. Material and Method: A total of 117 patients (pts.) were investigated the year after we changed our technique; a total of 152 pts were investigated in the reference period 2007. We investigated the identification rates for sentinel lymph nodes (SLN) identified scintigraphically and surgically as well as the rates of metastatic involvement (LN). Results: After PT injection, scintigraphic detection of SLN failed in 5/152 pts., and in a further 10 pts. SLN was not found at surgery. In 7 of 15 pts. in whom SLN was not detected, histology demonstrated nodal involvement. Metastases were found in the SLN of 28 of 137 pts. with successful detection of SLN; no other lymph nodes were affected in 21 of these pts. (75.0 % of pts. with positive SLN detection). With PA injection at least one SLN could always be detected using scintigraphy; only 2/117 SLN could not be found intraoperatively. Metastasis was found in SLN in 34/115 pts.; in 19/34 pts., metastatic involvement was limited to the SLN with no other lymph nodes involved (55.9 % of pts. with positive detection of SLN). Discussion: The detection rate for SLN was significantly higher using PA injection (98.3 % vs. 90.1 %). As axillary dissection was not done in SLN-negative patients, rates of false-negative detection cannot be determined. PA injection not only results in better detection rates, it also offers the advantage that the technique can be performed correctly regardless of tumour localisation.